EU enlargement and the constitutions of Central and Eastern Europe - Albi, Anneli (Cambridge studies in European law and policy., 2005)
This is the first book to comprehensively cover the adaptation of the constitution of Central and Eastern Europe for accession to the European Union. Key themes include sovereignty, legitimacy, supremacy, referendums, constitutional review, implication of the European Constitution, as well as constitutional issues of membership in NATO.